Transient surface photovoltage of p-type Cu3BiS3 (2010)
Thin films of Cu3BiS3 were prepared by coevaporation. Hall-effect, Seebeck-effect, and surface photovoltage measurements show that Cu3BiS3 is a p-type semiconductor with Hall-mobility, free carrier concentration, and thermo-electric power of 4?cm2/V?s, 2×1016?cm?3, and 0.73 mV/K, respectively. The work function was determined by Kelvin probe force microscopy to be (4.37±0.04)?eV before and (4.57±0.01)?eV after deposition of a thin In2S3 layer. Transient surface photovoltage measurements at variable excitation wavelength showed the importance of defect states below the band gap for charge separation and the opportunity for surface defect passivation by a very thin In2S3 layer. The band bending at the Cu3BiS3/In2S3 interface was obtained. The role of grain boundaries for charge transport and charge separation is discussed.